1995
DOI: 10.1038/375148a0
|View full text |Cite
|
Sign up to set email alerts
|

Serial triggering of many T-cell receptors by a few peptide–MHC complexes

Abstract: T lymphocytes can recognize and be activated by a very small number of complexes of peptide with major histocompatibility complex (MHC) molecules displayed on the surface of antigen-presenting cells (APCs). The interaction between the T-cell receptor (TCR) and its ligand has low affinity and high off-rate. Both findings suggest that an extremely small number of TCRs must be engaged in interaction with APCs and raise the question of how so few receptors can transduce an activation signal. Here we show that a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
879
1
16

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,050 publications
(946 citation statements)
references
References 25 publications
50
879
1
16
Order By: Relevance
“…This could result in the engagement of a higher number of TCR and other molecules on the surface of the T cell that are engaged in generating the activation signal cascade [36]. T cells have been found to "count" the number of TCR that are involved in the interaction with the APC, and a T cell becomes activated once a critical threshold number is reached [37,38]. In the case of such enhanced membrane interactions, DC should be able to more rapidly engage the critical number of TCR compared to B cells.…”
Section: Discussionmentioning
confidence: 99%
“…This could result in the engagement of a higher number of TCR and other molecules on the surface of the T cell that are engaged in generating the activation signal cascade [36]. T cells have been found to "count" the number of TCR that are involved in the interaction with the APC, and a T cell becomes activated once a critical threshold number is reached [37,38]. In the case of such enhanced membrane interactions, DC should be able to more rapidly engage the critical number of TCR compared to B cells.…”
Section: Discussionmentioning
confidence: 99%
“…peptides bound to MHC molecules expressed on APC [27,28]. The extent of TCR downregulation is dependent on the concentration and quality of the agonist displayed on the APC surface, but is not influenced by costimulatory molecules [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we evaluated the response to the melanoma target in terms of TCR down-regulation. For this experiment, we chose the only melanoma patient whose PHA line exhibited some degree of TCR downregulation versus the natural Melan-A [26][27][28][29][30][31][32][33][34][35] peptide, a prerequisite for melanoma cell recognition, and we selected the vitiligo patient exhibiting the most similar behavior. The results indicated that only vitiligo CTL were capable of TCR down-regulation in response to this stimulus (Fig.…”
Section: Tumor Reactivity Of Whole Melan-a-specific Cytotoxic T Lymphmentioning
confidence: 99%
“…In contrast, fibroblasts, muscle cells, and liver hepatocytes carry much lower quantities, sometimes 100 or fewer per cell. It was estimated that APC pulsed with high concentration (20 μM) of peptide displays ~7500 pMHC-I complex, and with low concentration (50 nM) display only ~100 pMHC-I complex (45). Normally, each nucleated cell expresses 4~6 different kinds of MHC-I.…”
Section: Molecular Basis Of Mhc-i/tcr Interactionmentioning
confidence: 99%